Pelanggaran Fiduciary Duty dan Misappropriation Oleh PT Asabri dan Barclays V Singularis: (Studi Komparatif Indonesia dan Inggris) - Muhammad Farrel Haristyanto (Pemuliaan Keadilan, 2025)
Fiduciary duty breaches and misappropriation are serious issues in corporate governance that can result in significant losses for companies and the state. This study aims to analyze the forms and mechanisms of legal accountability for fiduciary duty breaches and misappropriation through a comparative study of the cases of PT Asabri in Indonesia and Barclays v Singularis in the UK. The research method used is normative legal research with a conceptual, statutory, and comparative legal approach. The analysis was conducted on primary, secondary, and tertiary legal materials which were then presented qualitatively in the form of exploratory and argumentative descriptive narratives. The results of the study indicate that fiduciary duty is recognized in both legal systems but with different scopes. Where the English legal system can apply this obligation to third parties such as banks through the Quincecare duty, while in Indonesia it is limited to internal parties of the company. The concept of misappropriation is not explicitly mentioned in Indonesian law but is covered in various regulations through the terms embezzlement and abuse of authority. The PT Asabri case demonstrated systematic violations by internal management, resulting in losses reaching Rp 23.7 trillion, while the Barclays v. Singularis case demonstrated the bank's negligence in preventing misuse of client funds. The implications of this research highlight the need for regulatory harmonization and strengthened oversight mechanisms to prevent similar violations in the future.